1996
DOI: 10.1002/(sici)1099-0720(199602)10:1<41::aid-acp361>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

The spontaneous use of memory aids at different educational levels

Abstract: Three groups of students in different educational levels: 8th–9th grade students (average age 15); 10th–11th grade students (average age 16); and college students (average age 21), completed a metamemory questionnaire on the use of external, general, and formal memory aids in everyday life and study situations. Short‐term repetition, mental rehearsing, and summary elaboration were the most frequent aids. The least frequently used were those that require a special training to be used effectively (e.g. Digit‐let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…Past findings on other aspects of PM have shown a fairly consistent pattern, with females outscoring males on perceived task importance (Penningroth & Scott, 2013), strategy use (Soler & Ruiz, 1996;Uttl & Kibreab, 2011;Yoder & Herrmann, 2003), and actual performance (e.g., Huppert, Johnson, & Nickson, 2000;Maylor & Logie, 2010). Past findings on other aspects of PM have shown a fairly consistent pattern, with females outscoring males on perceived task importance (Penningroth & Scott, 2013), strategy use (Soler & Ruiz, 1996;Uttl & Kibreab, 2011;Yoder & Herrmann, 2003), and actual performance (e.g., Huppert, Johnson, & Nickson, 2000;Maylor & Logie, 2010).…”
mentioning
confidence: 88%
“…Past findings on other aspects of PM have shown a fairly consistent pattern, with females outscoring males on perceived task importance (Penningroth & Scott, 2013), strategy use (Soler & Ruiz, 1996;Uttl & Kibreab, 2011;Yoder & Herrmann, 2003), and actual performance (e.g., Huppert, Johnson, & Nickson, 2000;Maylor & Logie, 2010). Past findings on other aspects of PM have shown a fairly consistent pattern, with females outscoring males on perceived task importance (Penningroth & Scott, 2013), strategy use (Soler & Ruiz, 1996;Uttl & Kibreab, 2011;Yoder & Herrmann, 2003), and actual performance (e.g., Huppert, Johnson, & Nickson, 2000;Maylor & Logie, 2010).…”
mentioning
confidence: 88%
“…First, research has revealed a female advantage on several motivational variables including higher scores on conscientiousness (Soto et al 2011), greater certainty about career aspirations (Gutman and Schoon 2012), and a motivational boost to memory performance for Eur J Ageing (2013) 10:211-221 213 a list when it has a gender-matched label (e.g., a ''grocery list'' label; Colley et al 2002). Second, females have shown advantages on other aspects of prospective memory that are correlated with higher importance ratings, including more successful performance rates (Ceci and Bronfenbrenner 1985;Huppert et al 2000;Maylor and Logie 2010) and greater use of memory strategies (Penningroth and Scott unpublished manuscript;Soler and Ruiz 1996). Therefore, our tentative prediction for this hypothesis was that females would provide higher importance ratings for their real-life prospective memory tasks than males.…”
Section: Gender Differencesmentioning
confidence: 94%
“…Although spontaneous use of formal mnemonics is infrequent (Intons-Peterson and Fournier, 1986;Soler and Ruiz, 1996), this does not mean that selfgenerated mnemonics are more useful. For example, Wang and Thomas (2000) examined the effectiveness of the method of loci, the peg-word method, selfgenerated organizational and imagery mnemonics, and rote rehearsal in determining serial recall.…”
Section: Practical Issuesmentioning
confidence: 99%